The Effect of Perceived Risk, Benefit, and Ease of Credit on Credit-Making Decisions Among MSMEs in Sragen Regency - Mustofa, Rochman Hadi; Pamungkas, Leonny Noviyana Sakti; Karima, Mutiara; Zemafi, Okindy Dheawara (AIBPM Publisher, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are essential to economic growth MSMEs are considered a new economic wheel that can encourage the regional economy to contribute to employment This study aimed to examine the effect of perceived risk, benefits, and ease of credit on taking credit decision-making in MSMEs in the Sragen Regency. Data were collected from as many as 153 respondents who are MSMEs in Sragen Regency using a Likert scale questionnaire. The sampling technique used is random cluster sampling in each sub-district in Sragen Regency. The data analysis includes assumption, multiple linear regression, and hypothesis testing (t-test and F-test). The research results show that the perception of risk, the perception of benefits, and the ease of credit significantly affect the credit-making decisions of MSME actors in the Sragen Regency. This research implies that capital providers need to pay attention to the public's view of the risks, benefits, and convenience of credit by socializing, being more responsive and informative about criticism and suggestions, and providing solutions for MSMEs with financial problems.